Effects of KRN633, an Inhibitor of Vascular Endothelial Growth Factor Receptor-2 Tyrosine Kinase, on Vascular Development of Placenta and Fetus of Mid Pregnancy in Mice - Yoshiko Wada; Hiromi Ozaki; Naomichi Abe; Tohru Nagamitsu; Hiroaki Ohta; Tsutomu Nakahara; Kunio Ishii (Elsevier, 2010)
Inhibition of the vascular endothelial growth factor (VEGF) signaling pathway during pregnancy contributes to several pathologic pregnancies, such as hypertension, preeclampsia, and intrauterine growth restriction, but its effects on the fetus have not been fully examined. To determine how inhibition of the VEGF signaling pathway affects the fetal vascular development of mid pregnancy, we treated pregnant mice daily with either the VEGF receptor-2 (VEGFR-2) tyrosine kinase inhibitor KRN633 (300 mg/kg, p.o.) or the vehicle from 13.5 to 15.5 day of pregnancy. On the 16.5 day of pregnancy, the vascular beds in the placenta and several organs of the fetus were visualized by fluorescent immunohistochemistry. All mice treated with KRN633 appeared healthy, and total numbers of fetuses per litter were unaffected. However, weights of the placenta and fetus from KRN633-treated mice were lower than those from the vehicle-treated ones. No external malformations and bleeding were observed in the placenta and fetus, whereas immunohistochemical analyses revealed that the vascular development in labyrinthine zone of placenta and fetal organs examined (skin, pancreas, kidney, and lung) were impaired by KRN633 treatment. These results suggest that inhibition of the VEGF signaling pathway during mid pregnancy suppresses vascular growth of both the placenta and fetus without obvious health impairments of mother mice and increases the risk of induction of intrauterine growth restriction. Keywords:: fetus, intrauterine growth restriction, placenta, vascular endothelial growth factor (VEGF), vascular development